PERBANDINGAN NILAI ANALITIK DENGAN NILAI NUMERIC PADA ANALISA BALOK DI ATAS PONDASI ELASTIS - Minson Simatupang; Romy Tamburaka (Metropilar - Jurnal Ilmiah Fakultas Teknik, 2008)
Beam on elastic foundation analysis with sub grade reaction approach can be done either analytically or numerically. However, great possibility of both of this approach will give differ result. But the problem is whether this difference in properly limit or not. Analytically analysis had been done by Hetenyi, and numerically approach in this paper used Finite Difference Method (FDM). Beams that under analysis are finite beam with free end with loading conditions are concentrated load at an arbitrary point and two equal concentrated load symmetrically placed. For symmetrical load, both of this approaches give results that almost same, either displacements or bending moments. For concentrated load at an arbitrary point, both of this approach give difference results up to 16% in certain points of beam, especially bending moments. Key words: balok, pondasi elastis, beban terpusat